ChemInform Abstract: Heteroarene‐Directed Oxidative sp2 C—H Bond Allylation with Aliphatic Alkenes Catalyzed by an (Electron‐Deficient η5‐Cyclopentadienyl)rhodium(III) Complex. Issue 45 (October 2016) - Takahama, Yuji; Shibata, Yu; Tanaka, Ken
Abstract: A regioselective allylation of benzenes with aliphatic olefins is achieved using heteroarenes as directing groups under mild conditions.